Nano-selenium, silicon and H2O2 boost growth and productivity of cucumber under combined salinity and heat stress - Shalaby, Tarek A.; Abd-Alkarim, Emad; El-Aidy, Farouk; Hamed, El-Samahy; Sharaf-Eldin, Mohamed; Taha, Naglaa; El-Ramady, Hassan; Bayoumi, Yousry; dos Reis, André Rodrigues [UNESP] (Elsevier, 2021)
The production of cucumber under combined salinity and heat stress is a crucial challenge facing many countries particularly in arid environments. This challenge could be controlled through exogenous foliar application of some bio-stimulants or anti-stressors. This study was carried out to investigate the management and improving cucumber production under combined salinity and heat stress. Nano-selenium (nano-Se, 25 mg L-1), silicon (Si, 200 mg L−1) and hydrogen peroxide (H2O2, 20 mmol L−1) were foliar applied on cucumber plants as anti-stress compounds. The results revealed that studied anti-stressors improved growth and productivity of cucumber grown in saline soil regardless the kind of anti-stressor under heat stress. The foliar application of nano-Se (25 mg L−1) clearly improved cucumber growth parameters (plant height and leaf area) compared to other anti-stressor and control. Foliar Si application showed the greatest impact on enzymatic antioxidant capacities among the other anti-stressor treatments. This applied rate of Si also showed the greatest increase in marketable fruit yield and yield quality (fruit firmness and total soluble solids) compared to untreated plants. These increases could be due to increasing nutrient uptake particularly N, P, K, and Mg, as well as Se (by 40.2% and 43%) in leaves and Si (by 11.2% and 22.1% in fruits) in both seasons, respectively. The potential role of Si in mitigating soil salinity under heat stress could be referred to high Si content found in leaf which regulates water losses via transpiration as well as high nutrient uptake of other nutrients (N, P, K, Mg and Se). The distinguished high K+ content found in cucumber leaves might help stressed plants to tolerate studied stresses by regulating the osmotic balance and controlling stomatal opening, which support cultivated plants to adapt to soil salinity under heat stress. Further studies are needed to be carried out concerning the different response of cultivated plants to combined stresses.
Keywords: Antioxidants; Catalase; Economic evaluation; Electrolyte leakage; Peroxidase